2017
DOI: 10.18632/oncotarget.17927
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion-associated protein peroxiredoxin 3 promotes benign prostatic hyperplasia through autophagy suppression and pyroptosis activation

Abstract: Benign prostatic hyperplasia (BPH) is one of the most common diseases in the senior men and age plays an important role in the initiation and development of BPH. Mammalian cells primarily use the autophagy-lysosome system to degrade misfolded/aggregated proteins and dysfunctional organelles such as mitochondria and suppress pyroptosis, a type of cell death that stimulates inflammatory responses and growth of other cells around. Peroxiredoxin 3 (PRDX3) is the only mitochondrion-associated member of peroxiredoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Peroxiredoxin 3 (PRDX3) is an oxidation/reduction-related protein found in the mitochondria, which has been found to exhibit protective antioxidant effects and inhibit autophagy ( 12 , 13 ). PRDX3 has been reported to promote cancer cell survival by aiding cancer cells to escape cell oxidation, and the protein expression levels of PRDX3 has been negatively associated with autophagy ( 12 , 14 ). Previously, PRDX3 has been identified as a target protein of miR-383, and a negative association between the expression levels of miR-383 and PRDX3 was found ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxiredoxin 3 (PRDX3) is an oxidation/reduction-related protein found in the mitochondria, which has been found to exhibit protective antioxidant effects and inhibit autophagy ( 12 , 13 ). PRDX3 has been reported to promote cancer cell survival by aiding cancer cells to escape cell oxidation, and the protein expression levels of PRDX3 has been negatively associated with autophagy ( 12 , 14 ). Previously, PRDX3 has been identified as a target protein of miR-383, and a negative association between the expression levels of miR-383 and PRDX3 was found ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The average TFL from three repeats was used for each test and the maximal heating time was 20 s to avoid tissue damage. 15) Terminal Deoxynucleotidyl Transferase-Mediated Deoxyuridine Triphosphate Nick-End Labeling (TUNEL) Staining Paraffin-embedded spinal cord tissue sections were prepared for TUNEL staining. After deparaffinization and rehydration, the tissue sections were treated with 3% H 2 O 2 for 10 min at room temperature, then digested with proteinase K with 1 : 200 dilution in Tris-buffered saline (TBS) for 30 min at 37 °C.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Pyroptosis does not only occur during infectious diseases. Recent studies have shown that pyroptosis is also present in sterile inflammation, including diabetic atherosclerosis [23], acute liver injury [24], alcoholic hepatitis [25], diabetic cardiomyopathy [26], diabetic nephropathy [27], benign prostatic hyperplasia [28], Alzheimer's disease [29], temporal lobe epilepsy [30], renal ischemia/reperfusion [31], traumatic brain injury [32], ethanol-induced brain injury [33], and myocardial ischemia/reperfusion [34].…”
Section: Discovery Of Cell Pyroptosismentioning
confidence: 99%